Risk factors for multiorgan failure : a case-control study (1991)
The aim of this study was to identify factors associated with Multiple Organ Failure (MOF), and assess possible interactions between the risk factors identified as such. We studied 40 MOF cases and 120 controls, out of all the surgery and trauma patients who needed intensive care at our institution in a 24-month period. The univariate analyses showed that age, hypovolemic shock, massive volume administration (MVA), sepsis, and time of evolution before arriving to the hospital (TE) were significantly associated with MOF. Logistic regression analysis showed that neither age nor MVA were independently associated with MOF after adjusting for all of the other variables. Interactions seemed to be present between age, sepsis, and shock. We conclude that in our surgery and trauma ICU adult patient population, hypovolemic shock, sepsis, and TE are independent risk factors for MOF. The importance of the association between shock and sepsis is discussed, as well as the possible relevance of TE as a risk factor.